Postoperative Outcomes of Distal Pancreatectomy for Retroperitoneal Sarcoma Abutting the Pancreas in the Left Upper Quadrant - Kim, Kyeong Deok; Lee, Kyo Won; Lee, Ji Eun; Hwang, Jeong Ah; Jo, Sung Jun; Kim, Jinseob; Lim, So Hee; Park, Jae Berm (Frontiers in Oncology, 2021)
Background En bloc resection of the tumor with adjacent organs is recommended for localized retroperitoneal sarcoma (RPS). However, resection of the pancreas is controversial because it may cause serious complications, such as pancreatic fistula or bleeding. Thus, we evaluated the outcomes of distal pancreatectomy (DP) in pancreas-abutting RPS of the left upper quadrant (LUQ). Methods We retrospectively reviewed all consecutive patients who underwent surgery for RPS between September 2001 and April 2020. We selected 150 patients with all or part of their tumor located in the LUQ on preoperative computed tomography. Eighty-six patients who had tumors abutting the pancreas were finally enrolled in our study. Results Fifty-three patients (53/86; 61.6%) were included in the non-DP group, and 33 patients (33/86; 38.4%) were included in the DP group. Total postoperative complications and complication rates for those Clavien–Dindo grade 3 or higher were similar between the non-DP group and DP group (p = 0.290 and p = 0.550). In the DP group, grade B pancreatic fistulae occurred in 18.2% (6/33) of patients, but grade C pancreatic fistulae were absent, and microscopic pancreatic invasion was noted in 42.4% (14/33) of patients. During multivariate analysis, microscopic pancreatic invasion was deemed a risk factor for local recurrence (p = 0.029). However, there were no significant differences on preoperative computed tomography findings between the pancreatic invasion and non-invasion groups. Conclusion DP is a reasonable procedure for pancreas-abutting RPS located at the LUQ when both complications and complete resection are considered.